2018
DOI: 10.1039/c8ew00186c
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera coagulation as pretreatment prior to microfiltration for membrane fouling mitigation

Abstract: Coagulation pretreatment using Moringa oleifera in the microfiltration of river water achieved membrane fouling mitigation and filtered water quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Reduced alum dosages of less than 60% than previously used were required, lowering the cost of the overall process. Recently, Katalo et al [297] demonstrated the effectiveness of using Reproduced with permission from [33]. Copyright © 2013, Elsevier.…”
Section: Ecological Impacts Of Ro Pretreatmentmentioning
confidence: 99%
“…Reduced alum dosages of less than 60% than previously used were required, lowering the cost of the overall process. Recently, Katalo et al [297] demonstrated the effectiveness of using Reproduced with permission from [33]. Copyright © 2013, Elsevier.…”
Section: Ecological Impacts Of Ro Pretreatmentmentioning
confidence: 99%
“…Conventionally, the pretreatments comprise different methods, including disinfection, coagulation flocculation, and a filtration process, where all of them aim to remove foulants or their precursors [14]. As an example, Katalo et al [97] used Moringa oleífera seeds during pretreatment prior to microfiltration of river water. Moringa oleífera represents a non-toxic natural coagulant, which can be used in a conventional coagulation process.…”
Section: Alternative Novel Strategies In Biofouling Mitigationmentioning
confidence: 99%
“…Therefore, this approach not only represents a promising alternative in water treatment, but also its potentiality regards to the non-use of high-cost chemical coagulants, such as Al 2 (SO 4 ) 3 and FeCl 3 . Moreover, the seeds contain dimeric cationic proteins that substantially reduced membrane fouling by removing suspended solids and dissolving organic matter [97].…”
Section: Alternative Novel Strategies In Biofouling Mitigationmentioning
confidence: 99%
“…Despite a lot of research reports show that conventional coagulants have higher coagulation efficiency compared to seeds powder of Moringa Oleifera. However, Moringa Oleifera seeds coagulation has advantages over alum coagulation, such as posttreatment can be avoided for pH adjustment [35]. Moringa Oleifera is also a natural resource is an easy availability, eco-friendly, non-toxic, biodegradable; thus, the use of Moringa Oleifera allows avoiding many adverse effects of conventional coagulants such as alum.…”
Section: Characterization Of Moringa Oleifera Seed Extractmentioning
confidence: 99%